2019
DOI: 10.6007/ijarbss/v9-i8/6200
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Photographs of Addition in the School Environment

Abstract: Young children often face difficulty in acquiring Mathematics concepts. This study examined how photograph assist young children to understand the concept of early number and engage in addition activities within classroom learning. The study employed case study research design and involved six children (aged six years) in one preschool centre. Data was collected using observation, informal interviews and analysis of photograph produced by the focus group whilst engaged in various addition activities. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Mathematics teachers worldwide introduce a variety of representation forms during instruction, which may include concrete materials, visual images, i.e. pictures and photographs, written, and spoken symbols (Bakar & Karim, 2019;Elia, Gagatsis & Demetriou, 2007;Rosli, Goldsby & Capraro, 2015). Meanwhile, students create different representation forms to help them access ideas in mathematics, present their thinking, and find solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematics teachers worldwide introduce a variety of representation forms during instruction, which may include concrete materials, visual images, i.e. pictures and photographs, written, and spoken symbols (Bakar & Karim, 2019;Elia, Gagatsis & Demetriou, 2007;Rosli, Goldsby & Capraro, 2015). Meanwhile, students create different representation forms to help them access ideas in mathematics, present their thinking, and find solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Past researches have given emphasis to the benefits of using multiple representations (e.g. realworld situations, pictures, photographs, physical, verbal, and written symbols) for both the teaching and learning of mathematics, to ease the communication of mathematical ideas and thinking, to help understand concepts in mathematics, and to aid in problem-solving activities (Ahmad, Tarmizi & Nawawi, 2010;Ayub, Ghazali & Othman, 2013;Bakar & Karim, 2019;Elia et al, 2007;Rosli, Goldsby & Capraro, 2015). Despite the advantages of using multiple representations, as have been reported in previous studies, little is explored about young children's mathematical understanding, especially pertaining to the concept of addition.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of representation forms comprising diagrams (Diezmann & English, 2001;Pantziara, Gagatsis, & Elia, 2009;van Garderen et al, 2013), number lines (Bobis, 2007;Gonsalves & Krawec, 2014) and pictures (Stohlmann, Yang, Huang, & Olson, 2019;Woleck, 2001) have been conducted across various mathematical topics (numbers, operations and probability). With the recent advancement in technology, researchers have investigated the potential of technology-based representations to aid mathematical sense making (Bakar & Karim, 2019;Özmantar, Akkoç, Bingölbali, Demir, & Ergene (2010), particularly in the support of the learner's visualizations. Researchers involved in these studies assert that students employ representations, as various representations support the students' understanding of mathematical concepts and facilitate problem-solution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of studies investigating representation usage in the teaching and learning of mathematics, research involving young children and their use of representations in learning are scarce (Johns, 2015). Researchers have used children's' drawings to gain insights into their exposures, experiences and understanding of various mathematical concepts involving numbers and operations, mass, time and length (Bakar & Karim, 2019;MacDonald, 2010;MacDonald & Lowrie, 2011;Smith & MacDonald, 2009;Thomas, Mulligan, & Goldin, 2002). Mathematics educators and researchers around the globe have acknowledged the significance of representations in teaching and learning and have indicated that representations facilitate students in the communication and construction of mathematical thinking and ideas (Rosli, Goldsby, & Capraro, 2015;Ainsworth et.…”
Section: Introductionmentioning
confidence: 99%